Pengaruh musim terhadap kejadian pneumonia pada balita di Kabupaten Pelalawan - Harnani, Yessi; Hamidy, Rasoel; Sukendi, Sukendi; Afandi, Dedi (Dinamika Lingkungan Indonesia, 2022)
Pneumonia is a type of lower respiratory tract infection and the main cause of under-five mortality, especially in developing countries, with a mortality rate of 3 million each year. Pneumonia cases in children under five in Pelalawan Regency are quite high, namely 72.8% in 2018. Pneumonia is also influenced by climatic condi-tions and seasons. Parasites and disease vectors are very sensitive to climatic factors, especially temperature, humidity, and rainfall. The purpose of this study was to determine the effect of season on the incidence of pneumonia in children under five in Pelalawan District. This type of research is analytic observational with a cross sectional approach. The study population was all patients with pneumonia under five who were recorded in the registration of 12 Puskesmas in Pelalawan Regency in 2018-2019. The research sample uses total sam-pling. Data analysis uses the Vector Autorgressive (VAR) method on time series data with time level being monthly data. The results showed that the trend of the number of pneumonia cases fluctuated approximately every 2 months, this was caused by the influence of the season, namely the rainy season and dry season. Mostly in the rainy season the number of pneumonia cases tends to experience an increasing trend. Based on statisti-cal tests, it is known that seasonal variables (rainfall, rainy days, humidity and temperature) have no signifi-cant effect on the incidence of pneumonia in children under five, but the R Square value in the modeling above is quite good, namely 0.655, meaning that 65.5% of the diversity of pneumonia cases can be explained. by these variables while the rest is explained by other variables outside the model. For this reason, it is hoped that the Puskesmas will campaign for the '5 M' program, especially in the rainy season (opening ventilation, entry of light, entry of air, maintaining house cleanliness and increasing body immunity). It is suggested to the Pelalawan District Health Office to monitor climate factors on an ongoing basis in the context of the pro-gram to eradicate pneumonia in children under five.